Diagnostic Accuracy of Anticarbamylated Protein Antibodies in Established Rheumatoid Arthritis: A Monocentric Cross‐Sectional Study. Issue 7 (8th August 2019) - Erre, G. L.; Mundula, N.; Colombo, E.; Mangoni, A. A.; Sechi, L. A.; Oggiano, M.; Irde, R.; Zinellu, A.; Passiu, G.; Carru, C.
Abstract : Objective: To evaluate the diagnostic accuracy of anticarbamylated protein antibodies (CarP), alone and in combination with traditional biomarkers (rheumatoid factor [RF] and anticitrullinated peptide antibodies [ACPA]), in established rheumatoid arthritis (RA). Methods: A commercially available enzyme‐linked immunosorbent assay (ELISA) kit was used to assess CarP concentrations in serum samples of 200 established RA and 206 controls (115 healthy donors and 55 patients with other rheumatic diseases). Main outcome measures were sensitivity, specificity, and area under the curve (AUC; 95% confidence interval [CI]). Difference in accuracy was evaluated by comparison of the respective AUCs. Results: A serum CarP cut‐off of 1.47 ng/ml or more differentiated patients with RA from controls with 30% sensitivity, 97.1% specificity, and good accuracy (AUC[95%CI] = 0.83[0.79‐0.86], P < 0.0001). However, it showed moderate diagnostic accuracy in seronegative RA patients: sensitivity 17.9%, specificity 96.9%, and AUC (95% CI) = 0.69 (0.63‐0.75). The diagnostic accuracy of CarP_ACPA and CarP_RF combinations was significantly superior to that of ACPA and RF alone ( P < 0.0001 and P = 0.015, respectively), but not to that of ACPA_RF combination ( P = 0.089) In addition, the CarP_ACPA_RF combination did not improve the diagnostic accuracy of the ACPA_RF combination (AUC mean difference [95% CI] = 0.006 [−0.001 to 0.015], P = 0.10). The number of positive autoantibodies (0, 1, 2, or 3) was not significantly associated with moderate‐severe disease (Disease Activity Score‐28 [DAS‐28] > 3.2) in adjusted multiple regression analysis. Conclusion: CarP has good diagnostic accuracy in established RA but not in seronegative RA. The addition of CarP to ACPA and RF alone or in combination does not significantly enhance the diagnostic accuracy of ACPA_RF combination.